The US State-Building Failure in Afghanistan - Afzal, Osman Mohammed (European Scientific Journal, ESJ, 2021)
The almost nineteen years of international troops’ presence and their support and donations to strengthen a democratic state in Afghanistan were in vain. The state-building process began with the toppling of a retrogressive regime, which was considered the base of al-Qaeda leaders who masterminded the 9/11 attacks in the United States. Within 20 years, the Afghan government could not use the opportunities made available by the international community and the US presence in the country. Although most criticisms are leveled at the United States for this state-building failure, on the contrary, its roots in Afghanistan can be precisely traced back to the central government. In other words, the state-building failure in Afghanistan has inner flaws. The blame is not attributable to its international allies regarding the fragility of the state and decay of democracy. This article illustrates how state-building at the pivotal centre of democracy failed in Afghanistan. The main hurdles of state-building are also scrutinised.